Lexeme Formation of Kinship Greetings in the Pasemah Dialect (e-Journal of Linguistics, 2024)
Bengkulu is a province located on the west coast of Sumatra, which has six regional languages with nine different dialects. The most widely used dialect is the Serawai-Pasemah dialect, which has more than 400,000 speakers and is spread across various areas in Bengkulu Province to South Sumatra Province. This Serawai-Pasemah dialect is part of the Malayic dialect, whose hallmark is a unique greeting system because it is used to respect and show close kinship. A greeting is a set of words, morphemes, phrases, or expressions to greet or start a conversation. This study focuses on lexeme formation on kinship greetings and is limited to the Pasemah dialect. The research design is descriptive qualitative. The data source is three informants who are native speakers of the Pasemah dialect. Using the content analysis technique, the research results show that the lexemes formation in Pasemah kinship greetings is found only in affixation, clipping, compounding, and reduplication.
Keywords: Bengkulu Language; Kinship Greetings; Lexeme Formation; Pasemah Dialect